2009
DOI: 10.1038/sj.bjc.6604878
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine-oxaliplatin combination for ovarian cancer resistant to taxane-platinum treatment: a phase II study from the GINECO group

Abstract: Advanced ovarian carcinoma in early progression (o6 months) (AOCEP) is considered resistant to most cytotoxic drugs. Gemcitabine (GE) and oxaliplatin (OXA) have shown single-agent activity in relapsed ovarian cancer. Their combination was tested in patients with AOCEP in phase II study. Fifty patients pre-treated with platinum -taxane received q3w administration of OXA (100 mg m -2 , d1) and GE (1000 mg m -2 , d1, d8, 100-min infusion). Patient characteristics were a : median age 64 years (range 46 -79),and 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…However, once combined with other cytotoxic agents, response rates were significantly higher: combination therapy with any cytotoxic agents versus monotherapy, 27.2 vs. 6.1%, odds ratio 5.79, 95%CI 2.45–13.7, p<0.0001 (Figure 2). Gemcitabine-based therapy combined with epirubicin (48.1%, p<0.0001),13 with pegylated liposomal doxorubicin (28.7%, p<0.0001),14–16 with oxaliplatin (28.2%, p=0.0001),1718 or with cisplatin (21.7%, p=0.003)1920 demonstrated significantly higher response rates than treatment with gemcitabine alone. Combination therapy with gemcitabine and pegylated liposomal doxorubicin also showed a higher response rate than monotherapy with pegylated liposomal doxorubicin alone although it did not reach statistical significance (28.7 vs 19.8%, p=0.087).…”
Section: Approaches For Treating Platinum Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…However, once combined with other cytotoxic agents, response rates were significantly higher: combination therapy with any cytotoxic agents versus monotherapy, 27.2 vs. 6.1%, odds ratio 5.79, 95%CI 2.45–13.7, p<0.0001 (Figure 2). Gemcitabine-based therapy combined with epirubicin (48.1%, p<0.0001),13 with pegylated liposomal doxorubicin (28.7%, p<0.0001),14–16 with oxaliplatin (28.2%, p=0.0001),1718 or with cisplatin (21.7%, p=0.003)1920 demonstrated significantly higher response rates than treatment with gemcitabine alone. Combination therapy with gemcitabine and pegylated liposomal doxorubicin also showed a higher response rate than monotherapy with pegylated liposomal doxorubicin alone although it did not reach statistical significance (28.7 vs 19.8%, p=0.087).…”
Section: Approaches For Treating Platinum Resistancementioning
confidence: 99%
“…Current active members of available platinum agents include cisplatin, carboplatin, and oxaliplatin. In our analyses of published studies, 10 (16.7%) of the 60 clinical studies used platinum agents for patients with platinum resistance 1720, 30–35. Among clinical trials, 6 (10%) studies used platinum-based therapies such as cisplatin (n=3),1920, 30 carboplatin (n=1),31 and oxaliplatin (n=2) 1718.…”
Section: Approaches For Treating Platinum Resistancementioning
confidence: 99%
“…In many cases drug-cocktails or sequenced therapeutic combinations of natural, synthetic or semi-synthetic chemotherapeutic agents have shown a great promise for treating cancer more effectively by avoiding or overcoming a very usual phenomenon of single drug induced resistance capability of the cancer cells. [1115] In our study we have used the combinations of two different physical inputs of sound and light for activating a combined anticancer sensitizer, namely TiO 2 + 5-ALA, more effectively.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of grade 3 to grade 4 neutropenia was 33%. 21 Therefore, retreating with a regimen containing a platinum agent has shown a wide range of response rates 22 and further emphasized in a pooled analysis of the AGO-OVAR (Arbeitsgemeinschaft Gynaekologische Onkologie Ovarialkarzinom) and ICON (International Collaborative Ovarian Neoplasm) studies, which demonstrated that paclitaxel plus platinum was an improvement over platinum alone both in PFS and OS. 23 The CALYPSO (Caelyx in Platinum Sensitive Ovarian patients) study has now shown a longer PFS when liposomal doxorubicin with carboplatin is compared with paclitaxel and carboplatin in these platinum-sensitive patients (11.3 vs 9.4 months), 24,25 and the OCEANS (Ovarian Cancer Study Comparing the Efficacy and Safety of Chemotherapy and Anti-Angiogenic Therapy in Platinum-Sensitive Recurrent Disease) study indicates a lengthening of PFS when bevacizumab in combination with carboplatin and gemcitabine for platinum-sensitive patients (12.4 months vs 8.4 months).…”
Section: Discussionmentioning
confidence: 99%